Penerapan Analisis Swot Dalam Meningkatkan Program Pembinaan Kemandirian Bagi Warga Binaan Pemasyarakatan Di Lapas Perempuan Kelas II A Medan - Aulia Shirly (Universitas Hamzanwadi, 2021)
In this research, researchers aimed to identify strengths and weaknesses (internal environment) as well as opportunities and threats (external environment) and discuss problems through SWOT analysis (Strengths, Weaknesses, Opportunities and Threats) at Class II A Women's Prison in Medan. The research method used is descriptive qualitative research with data collection techniques through observation, interviews, and literature study. The results showed that the development program at the Class II A Women's Prison in Medan was still not optimal. There were still several obstacles that hindered the process of the self-reliance development program then analyzed using SWOT analysis on self-reliance development to produce data on what are the strengths, weaknesses, opportunities, and threats in the process of self-reliance development at the Class II A Women's Prison in Medan